Microsurgical treatment of posterior inferior cerebellar aneurysms based on angioarchitecture supplemented by high-resolution vessel wall MRI: a case series report. Issue 4 (6th April 2022) - Yang, Zixiao; Song, Jianping; Quan, Kai; Li, Peiliang; An, Qingzhu; Shi, Yuan; Liu, Peixi; Yu, Guo; Tian, Yanlong; Zhou, Liangfu; Zhu, Wei
Abstract : Background: Surgical treatment of posterior inferior cerebellar artery (PICA) aneurysms is challenging because many are nonsaccular and atherosclerotic. We report our tailored approach to PICA aneurysms, which is based on angioarchitecture supplemented by high-resolution vessel wall MRI (HR-VW MRI) findings. Methods: From March 2010 to September 2020, 27 patients with 29 PICA aneurysms underwent surgical treatment in our institution. Since October 2016, HR-VW MRI has been used for aneurysmal wall assessment. Clinical characteristics, radiological data and surgical outcomes were analysed. Results: Nineteen proximal PICA aneurysms (vertebral artery (VA), P1, P2 and P3) were treated using the far-lateral approach. Ten distal PICA aneurysms (P4, P5) were treated using the suboccipital midline approach. Direct clipping or clip reconstruction was achieved in 19 aneurysms. Ten were trapped in conjunction with extracranial–intracranial or intracranial–intracranial bypass, including three occipital artery-PICA reimplantations, three PICA-VA reimplantations, two PICA-PICA side-to-side anastomoses, one PICA-PICA reimplantation and one PICA-PICA reanastomosis. All aneurysms were eventually completely obliterated and all bypasses remained patent. At the last follow-up, 26 patients (96.2%) achieved a good outcome (modified Rankin Scale score <3). Eight patients underwent HR-VW MRI. Among these, the six aneurysms with focal wall enhancement required bypass and the two with negative enhancement were successfully clipped. Conclusion: PICA aneurysms have a higher frequency of complex features such as large or giant size and fusiform or dissecting morphology. Favourable outcomes were achieved with individualised microsurgical strategies based on angioarchitecture. HR-VW MRI may be used as a promising technique to predict aneurysmal atherosclerosis.